Influence of solar ultraviolet-B radiation in New Zealand on white clover (Trifolium repens L.), ryegrass (Lolium perenne L.) and pea (Pisum sativum L.) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Agricultural Science at Massey University, Palmerston North, New Zealand - Hofmann, Angelika (Massey University, 2002)
New Zealand pasture plants have been exposed to increasing levels of ultraviolet-B radiation (UV-B) as a result of stratospheric ozone depletion during recent years. Thus far, there has been only limited published information on UV-B effects on pasture plants growing under field conditions. This study set out to investigate effects of natural solar UV-B radiation in the field for the pasture species white clover (Trifolium repens L.) and ryegrass (Lolium perenne L.) and compared those with pea (Pisum sativum L.), another economically important crop. Contrasting UV-B levels were created with two filter systems, using UV-B-absorbing glasshouse polythene film and UV-B-transmitting perspex glass. A further treatment included open plots that were not covered by filters. Ambient UV-B irradiance levels were recorded daily during the experimental period in summer from early December 1995 to late February 1996. The pasture species were investigated in monoculture as well as in their typical association in an established sward that was regularly grazed by sheep. Morphological measurements included leaf expansion, leaf initiation, leaf senescence, stem elongation, above-ground biomass and aspects of plant reproduction. To identify possible responses related to UV-B protection, measurements included specific leaf mass (SLM), accumulation of UV-absoibing compounds and of anthocyanins. The highest UV-B levels occurred during the early- and midsummer period from mid December to late January. Clouding reduced UV-B irradiance by more than 70%. The UV-B-absorbing treatment reduced ambient UV-B levels by about 90%, and the transmitting filters by about 25%. Results from the monoculture trials revealed interspecific differences in UV-B sensitivity between the three plant species tested. Ryegrass and white clover appeared UV-B-sensitive in a number of vegetative morphological aspects, while pea generally displayed UV-B tolerance. Most features of UV-B sensitivity in the two pasture species were recorded during midsummer in January, with young plant pans particularly affected by the UV-B-transmitting treatments. The area of young white clover leaves was reduced by about 20%, and the length of young internodes by more than 25%. Solar UV-B increased the number of senescing ryegrass leaves in January and induced white clover inflorescence formation in February. Inflorescence numbers were also increased in pea under UV-B-transmitting filters. While there was no clear relationship between SLM and UV-B susceptibility, the biochemical studies suggest that the interspecific differences in UV-B sensitivity may be due to differences in the accumulation of UV-absorbing compounds and of anthocyanins. Average levels of UV-absorbing compounds across treatments were about 50% higher in pea than in the two pasture species. Furthermore and in contrast to the pasture species, pea showed the highest levels of anthocyanins under solar UV-B in January. The results from the sward trials were in general agreement with the findings from the monoculture studies, showing that morphological sensitivity under the UV-B-transmitting treatments could also be detected for white clover and ryegrass when grown in association. This was reflected in a reduction of white clover leaf area and of leaf elongation in mature ryegrass tillers by 13%, and by more than 20% in young ryegrass tillers. The effects on the two species under pasture conditions were also reflected in whole sward measurements, showing decreases in sward height of about 15% and in herbage accumulation of about 20% under UV-B-transmitting filters. In conclusion, the findings from this study show that near-ambient solar UV-B levels can affect the morphology of the two most commonly sown pasture plant species in New Zealand. In contrast, pea showed tolerance to UV-B and this may at least be partly due to higher intrinsic levels of UV-absorbing compounds.
Keywords: New Zealand; Effect of ultraviolet radiation on plants; Ultraviolet radiation; Physiological effect